Assessing the impact of critical care training on pharmacy students in Egypt: a pre-post study - Hebatallah Ahmed Mohamed Moustafa; Alaa Essawy Hamid; Gehad Hassoub; Amira B. Kassem (BMC Medical Education)
Abstract Background Transition to independent pharmacy practice is challenging. Undergraduate and postgraduate pharmacy students in low-to-middle-income countries (LMICs) currently receive minimal experiential learning in critical care. Objective To assess the critical care training course’s impact on pharmacy students’ knowledge, self-efficacy, and self-esteem, as well as their satisfaction with the course. Method In a pre-post interventional study, pharmacy students took a 10-day critical care training course with experiential learning. They completed a knowledge questionnaire covering various critical care topics, the 18 questions Pharmacy Self-efficacy and Self-esteem Study Questionnaire, and a satisfaction questionnaire. Data was analyzed using IBM SPSS version 20.0. Results A total of 72 trainees participated in the study. The average score for pre-course self-efficacy and self-esteem significantly increased post-course, with a median (IQR) of 3.75 (3.50–3.94) compared to 3.56 (3.28–3.78) pre-course, with a p-value of less than 0.05. Furthermore, their overall knowledge score significantly increased from baseline to post-course, with the median (IQR) rising from 0.53 (0.50–0.61) to 0.98 (0.97–1.0), with a p-value of less than 0.05. Their course satisfaction average total score was 45.08 (SD ± 5.41) (on a scale of 10–50). Conclusion The present study provides clear evidence that integrating this critical care training course into a structured curriculum for pharmacy students using experiential learning can act as a facilitator of knowledge enrichment, increase their self-esteem and self-efficacy, and make them satisfied with learning. Larger long duration studies are needed to support this evidence.